Clinical profiles of 710 premenopausal women with adenomyosis who underwent hysterectomy. Issue 2 (22nd October 2013) - Li, Xuelian; Liu, Xishi; Guo, Sun‐Wei
Abstract Aim The aim of this study was to determine the frequency of various symptoms and their associated characteristics in women with adenomyosis who underwent hysterectomy, and to determine which symptoms are likely to go with which others in these patients. Material and Methods In 2007, 1697 consecutive patients underwent hysterectomy in our hospital. Among them, 734 (43.3%) were histologically confirmed to have adenomyosis, and 710 of them were premenopausal. The medical charts of all 734 patients were retrieved, and their demographic, clinical information and postoperative findings were recorded. We used the Verbal Descriptor Scale to measure the preoperative severity of dysmenorrhea. The Apriori Algorithm was used for mining the association of different symptoms. Results Among the 710 premenopausal patients, only 4.5% of them had no symptoms. Dysmenorrhea was the most common complaint, occurring in 81.7% of patients. Dysmenorrhea co‐occurred most frequently with menorrhagia. The presence of adhesion, presence of endometriosis, complaint of menorrhagia, longer duration of disease, gravidity, palpable pain during pelvic examination, and diffuse adenomyosis were positively associated with the severity of dysmenorrhea. Age, severity of dysmenorrhea, and complaint of metrorrhagia were positively associated with the risk of menorrhagia. Conclusions Dysmenorrhea is the most common complaint in women with adenomyosis, which often goes with that of menorrhagia. Adenomyosis often co‐occurs with endometriosis and leiomyomas. Various factors are associated with the risk of having different symptoms.